Blunt Right ICA Biffle Grade IV Injury in a Case of Polytrauma: Successfully Managed by Decompressive Craniectomy. (Anwer Khan Modern Medical College Journal, 2017)
Traumatic brain injury (TBI) is common in our country. In our daily practice we are successfully managing TBI. But in some cases patient clinical conditions do not correlate with neuroimaging specially CT scan of brain. These injuries are generally missed due to lack of awareness, paucity of findings in the initial CT brain, and in some cases due to delayed clinical manifestation. For more effective and appropriate management especially blunt cerebrovascular injury we are reporting this. Moreover in RTA poly trauma make our choice of treatment more difficult but rational approach can safe a patient as did in our case.Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 76-78